Trend and spatial analysis of hand, foot and mouth disease (HFMD) in Pulau Pinang between 2017-2022 - Hamedin, Mohamad Afiq Amsyar (2023)
Background: Hand-foot-mouth disease (HFMD) is a major global public health issue, especially in Asian Pacific Region including, Malaysia and particularly affects children. Recognizing high-risk areas early on and understanding how the disease spreads can help public health authorities effectively prevent HFMD outbreaks from occurring. Objective: This study aimed to determine incidence of HFMD in Pulau Pinang, map the incidence at subdistrict level, estimate the spatial intensity of HFMD infections, test for presence of spatial autocorrelation and identify hotspots of HFMD infections. Methodology: This was a cross sectional study using secondary data from Communicable Diseases Control Information System (CDCIS) E-Notification Version 2011 governed by State Health Department of Pulau Pinang. Data on population in Pulau Pinang was obtained from Department of Statistic Malaysia. The coordinates were converted into the format of projected system Kertau Rectified Skewed Orthomorphic (RSO) Malaya (EPSG:3168). Incidence of HFMD was calculated at subdistrict level and point pattern analysis conducted using Kernel Density Estimates and Nearest Neighboring Index (NNI). The study also analyses presence of spatial autocorrelation and hot spot analysis to distinguish spatial risk at subdistrict level. Analyses were done using gtsummary, tmap, spdep, spatialeco and spastat package in R Software Version 4.2.3 Result: There was total of 15 586 reported HFMD cases between 2017 until 2022. Except year 2020 and 2021, increment of incidence of HFMD was seen with highest incidence reported in 2022 at 24.81 cases per 1000 population. Kernel Density Estimates (KDE) analysis revealed HFMD cases centered at District of Timur Laut, particularly in the subdistrict of Bandar Georgetown and Mukim 13, and began to spread over Barat Daya and pockets of the Seberang Perai area of the state. There was evidence of spatial cluster of HFMD based on NNI (0.21-0.50) for all studied years. The Global Moran I statistic, ranging from 0.21 to 0.38, suggests the presence of spatial autocorrelation in all the years studied. The Local Indicator of Spatial Autocorrelation (LISA) map revealed that the areas with high-high (H-H) values were mainly clustered along the eastern coast of Penang Island, indicating hotspots for HFMD. Additionally, there was a decrease in the number of low-low (L-L) regions, which were replaced by high-low (H-L) regions, particularly in the Seberang Perai area. This indicates a growing risk of HFMD infections in that region. Conclusion: The spatial intensity, spatial autocorrelation, and significant hotspot regions primarily located in urbanized and newly developed areas in Pulau Pinang. These areas are characterized by high population density, industrial activities, and settlements. The findings from studying the incidence and spatial patterns of HFMD infections can serve as an additional parameter for HFMD surveillance activities and formulating targeted preventive actions.